Additional Mental Health Training and Resources Needed for Nurses in the ED. Issue 44 (January 2015) - Vinall, Maria
Training and support, in the form of both physical and human resources, are needed to assist emergency department (ED) nurses in meeting the needs of patients with mental illness. Individuals seeking assistance for a mental health crisis often present in the ED. This article presents results from a study that assessed whether ED nurses have adequate knowledge, resources, skills, and confidence to meet the needs of patients with mental illness, and reported the nurses' perceptions and experiences in this area.